Suppressed oxygen evolution during chlorate formation from hypochlorite in the presence of chromium(VI). Issue 5 (5th February 2019) - Endrődi, Balázs; Sandin, Staffan; Wildlock, Mats; Simic, Nina; Cornell, Ann
Abstract: Background: Chromium(VI) is a crucial electrolyte component in industrial chlorate production. Due to its toxicity, it urgently needs to be abandoned and its functions fulfilled by new solutions. In the industrial production of sodium chlorate, homogeneous decomposition of the hypochlorite intermediate to chlorate is a key step. As a competing loss reaction, hypochlorite can decompose to oxygen. How chromium(VI) affects these reactions is not well understood. Results: This work shows, for the first time, that chromium(VI) selectively accelerates the chlorate formation from hypochlorite both in dilute and concentrated, industrially relevant solutions. The effect of the ionic strength and the specific contribution of different electrolyte components were systematically studied. By simultaneously measuring the concentration decay of hypochlorite (UV–vis spectroscopy) and the oxygen formation (mass spectrometry), both the rate and the selectivity of the reactions were evaluated. Conclusion: In the presence of chromium(VI) the hypochlorite decomposition is described by the sum of an uncatalyzed and a parallel catalyzed reaction, where oxygen only forms in the uncatalyzed reaction. When removing chromium(VI), the homogeneous oxygen formation increases, causing economic and safety concerns. The need for a catalyst selective for chlorate formation is emphasized. © 2018 The Authors. Journal of Chemical Technology & Biotechnology published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.